CAAD and e-Learning: a Blended Approach - Pedro Neto (2008)
This case study was conducted by the senior lecturer in charge of the Computer Architectural Aided Design (CAAD) course, with the support and active collaboration of Instituto de Recursos e Iniciativas Comuns da Universidade do Porto (IRICUP). CAAD is an optional course for fifth-year students at the Faculty of Architecture of the University of Porto (FAUP). he course evolves in a collaborative environment (teacher/student and student/student) to facilitate the exchange of ideas and design communication and the creation of an efficient learning context. The theoretical and empirical bases of the course highlight the concern that the potential of computers for communicating urban design should be used with critical awareness. Thus, the goal is to point out specific attributes for different representation methods and make students think about why they use different computer techniques and representations for presenting their design. Within this context, it was important to adopt a set of teaching methods, communication techniques and specific software that enabled this course to differ from the traditional methods of teaching: demonstrative lecturing and students adopting a more or less passive role in the process. After innovating in relation to the tools used in the process of teaching/learning, one should not forget to change the methodologies to encourage students to engage in discussion and adopt an active role in the process. In my point of view, this must be the main goal. This was achieved through several types of information and software utilities, not only from a distance perspective, but also in relation to the face-to-face interaction in classes, where a problem solving approach for each group as their communication projects evolved was used. The results from this case study highlighted, among other things, that the learning process that emerges from the creative use of an e-learning platform strengthens the teachers' capacity to work as a team. This means that this technology worked as a real catalyst for a new teacher/student interaction, making communication much easier and giving the students a more active role in the learning process.